Analysis Of The Effectiveness Of Google Workspace For Education Training On The Improvement Of Teachers' Digital Competence - Rina Wati; Jonni Mardizal; M Giatman; Hansi Effendi (STKIP Singkawang, 2025)
In the era of educational digital transformation, enhancing teachers' digital competence has become a critical challenge. This study investigates the effectiveness of Google Workspace for Education training in improving the digital competence of teachers at SMA Negeri 11 Padang, a school preparing to become a Google Reference School. A quantitative descriptive method was employed, involving 40 teachers as respondents through a structured questionnaire. Data were analyzed using descriptive statistics, normality and linearity tests, and Pearson correlation. The results reveal a strong positive correlation (r = 0.891, p < 0.001) between the training and teachers’ digital competence, indicating that the training significantly improves their ability to utilize digital tools for teaching, collaboration, and classroom management. Furthermore, the training content, methods, and teacher engagement were found to play critical roles in shaping effective outcomes. These findings support the notion that structured and pedagogically aligned training is essential for equipping educators with relevant digital skills. It is concluded that Google Workspace training serves as an effective strategic intervention for advancing digital teaching competence in secondary education